The Tableau Workshop - Gupta, Sumit; Gupta, Sumit; Pinto, Sylvester; Sankhe-Savale, Shweta (Packt Publishing, 2022)
Learn how to bring your data to life with this hands-on guide to visual analytics with TableauKey FeaturesMaster the fundamentals of Tableau Desktop and Tableau PrepLearn how to explore, analyze, and present data to provide business insightsBuild your experience and confidence with hands-on exercises and activitiesBook DescriptionLearning Tableau has never been easier, thanks to this practical introduction to storytelling with data. The Tableau Workshop breaks down the analytical process into five steps: data preparation, data exploration, data analysis, interactivity, and distribution of dashboards. Each stage is addressed with a clear walkthrough of the key tools and techniques you'll need, as well as engaging real-world examples, meaningful data, and practical exercises to give you valuable hands-on experience.As you work through the book, you'll learn Tableau step by step, studying how to clean, shape, and combine data, as well as how to choose the most suitable charts for any given scenario. You'll load data from various sources and formats, perform data engineering to create new data that delivers deeper insights, and create interactive dashboards that engage end-users.All concepts are introduced with clear, simple explanations and demonstrated through realistic example scenarios. You'll simulate real-world data science projects with use cases such as traffic violations, urban populations, coffee store sales, and air travel delays.By the end of this Tableau book, you'll have the skills and knowledge to confidently present analytical results and make data-driven decisions.What you will learnBecome an effective user of Tableau Prep and Tableau DesktopLoad, combine, and process data for analysis and visualizationUnderstand different types of charts and when to use themPerform calculations to engineer new data and unlock hidden insightsAdd interactivity to your visualizations to make them more engagingCreate holistic dashboards that are detailed and user-friendlyWho this book is forThis book is for anyone who wants to get started on visual analytics with Tableau. If you're new to Tableau, this Workshop will get you up and running. If you already have some experience in Tableau, this book will help fill in any gaps, consolidate your understanding, and give you extra practice of key tools.